Complications of Percutaneous Vertebroplasty: A Pictorial Review - Mislav Cavka; Domagoj Delimar; Robert Rezan; Tomislav Zigman; Kresimir Sasa Duric; Mislav Cimic; Ivo Dumic-Cule; Maja Prutki (Medicina, 2023)
Percutaneous vertebroplasty is a minimally invasive treatment technique for vertebral body compression fractures. The complications associated with this technique can be categorized into mild, moderate, and severe. Among these, the most prevalent complication is cement leakage, which may insert into the epidural, intradiscal, foraminal, and paravertebral regions, and even the venous system. The occurrence of a postprocedural infection carries a notable risk which is inherent to any percutaneous procedure. While the majority of these complications manifest without symptoms, they can potentially lead to severe outcomes. This review aims to consolidate the various complications linked to vertebroplasty, drawing from the experiences of a single medical center.